إنعكاسات المنشور الوزاري ( 838) في الإنخراط في مسمى تطوير الرياضة المدرسية ( ولاية سعيدة) - بوشيبة, أحمد (Institut d'Éducation Physique et Sportive - Mostaganem 2024/2025, 2025)
تهدف الدراسة التي بين أيديكم إلىالتعرف على انعكاسات المنشور الوزاري المتعلق بتطوير الرياضة المدرسية على مستوى الانخراط في ممارستها داخل الوسط التربوي الجزائري. ولأجل ذلك اتبعنا المنهج الوصفي بالأسلوب المسحي بالإعتماد على الاستبيان كأداة لجمع البيانات، حيث تمثلت العينة في ( 143) أستاذ تربية بدنية ورياضية بنسبة بلغت 41.93% من المجتمع الأصلي. وجاءت أهم نتائج البحث بأنالمنشور الوزاري الأخير المتعلق بتطوير الرياضة المدرسية كان له انعكاس إيجابي واضح على مستوى الانخراط في الرياضة المدرسية. // // // // This study aims to identify the implications of the ministerial circular related to the development of school sports on the level of engagement in the practice of school sports within the educational environment in Algeria. For this purpose, we followed the descriptive survey method using the questionnaire as a tool for data collection. The sample consisted of ( 143) physical education and sports teachers (41.93% of the original population). The most important findings of the research were that the recent ministerial circular related to the development of school sports had a clear positive impact on the level of engagement in school sports.
MEPS-2025-17
Keywords: المنشور الوزاري - الرياضة المدرسية -الوسط التربوي // // - Ministerial circular - School sport - Educational environment